Evaluation of the Mechanical Properties of Different Dental Resin-Based Materials After Submersion in Acidic Beverages - Răzvan Constantin Brânzan; Ionuț Tărăboanță; Cristina Angela Ghiorghe; Simona Stoleriu; Vlad Cârlescu; Andra Claudia Tărăboanță-Gamen; Sorin Andrian (Dentistry Journal)
Background: The aim of this study was to evaluate the influence of acidic beverages on the mechanical properties of various dental resin-based materials. Methods: A total number of 160 samples were prepared using four types of resin-based materials—Group A (n = 40): flowable composite, Group B (n = 40): heavy-flow composite, Group C (n = 40): resin-based sealant and Group D (n = 40): nano-hybrid composite. Then, the samples were distributed into four subgroups according to the submersion solution: a (n = 10): artificial saliva, b (n = 10): coffee, c (n = 10): cola and d (n = 10): red wine. The Vickers microhardness, Young’s modulus of elasticity and scratch resistance were assessed using a CETR UMT-2 tribometer. Results: The obtained results showed that 14-day submersion of the resin-based materials in coffee, cola and red wine solutions significantly (p < 0.05) decreased the microhardness values (VHN), Young’s modulus of elasticity and scratch resistance. Fourteen days of storage in coffee decreased the microhardness values of flow resin from 117.5 to 81.59 VHN (p < 0.001) whereas the values of the nanohybrid resin decreased from 125.5 to 89.4 (p < 0.001). The elasticity modulus of the heavy flow resin showed a decline from 15.57 to 10.50 GPa after 14 days’ submersion in coffee (p < 0.001), and from 21.29 to 13.10 GPa for the nanohybrid resin after immersion in cola (p < 0.001). For the scratch test, the resin-based sealant showed a significant decrease after 14 days of storage in coffee, from 0.34 to 0.02 units. Conclusions: The submersion of conventional nanohybrid, flowable, heavy-flow composite resins and resin-based sealants in coffee, cola and red wine solutions changes the mechanical properties (Young’s modulus of elasticity, Vickers microhardness and scratch resistance). The most resistant resin-based material to acid attack was the conventional nanohybrid composite resin, followed by heavy flow resin, flowable resin and resin-based sealant.